Helminths infecting Rhinella diptycha Cope, 1862 and Rhinella granulosa Spix,1824 from northeastern Brazil. - SOUSA, L.F.S, Leonardo Fernando da Silva Sousa (2024)
Brazil is the country with the highest diversity and description rate of amphibian species in the world. The genus Rhinella has 100 species of small, medium and large animals, insectivorous, terrestrial or semi-aquatic and nocturnal. Rhinella diptycha Cope, 1862 and Rhinella granulosa Spix,1824 are widely distributed throughout the Brazilian Northeast. Despite their diversity and wide distribution, infectious diseases caused by helminths have caused a reduction in the populations of these animals. In this study, we determined the parasitic fauna of R. diptycha and R. granulosa recorded in the states of Piauí and Maranhão, Northeast Brazil. We collected 60 specimens, 30 of R. diptycha and 30 of R. granulosa, of which 78% of the total (n = 47 individuals) were infected with helminths. The helminths found were Aplectana membranosa Schneider, 1866, Cosmocerca sp. Diesing, 1861, Rhabdias sp Stiles & Hassal, 1905, Oswaldocruzia sp. Travassos, 1917, Physaloptera sp. Rudolphi, 1819, and Cylindrotaenia americana Jewell, 1916. Cosmocerca sp. represents the first record of this taxon parasitizing R. diptycha. Our findings contribute to expanding knowledge about the diversity of helminths parasitizing bufonids in the Northeast region of Brazil. More studies are still needed to understand the mechanisms associated with this parasite-host relationship.